Combining Network Pharmacology and Experimental Validation to Study the Action and Mechanism of Water extract of Asparagus Against Colorectal Cancer - Liang, Huiling; Li, Yanju; Wang, Feiqing; Zhao, Jianing; Yang, Xu; Wu, Dan; Zhang, Chike; Liu, Yanqing; Huang, Jie; Su, Min; He, Zhixu; Liu, Yang; et al. (Frontiers in Pharmacology, 2022)
Asparagus (ASP) is a well-known traditional Chinese medicine with nourishing, moistening, fire-clearing, cough-suppressing, and intestinal effects. In addition, it exerts anti-inflammatory, antioxidant, anti-aging, immunity-enhancing, and anti-tumor pharmacological effect. The anti-tumor effect of ASP has been studied in hepatocellular carcinoma. However, its action and pharmacological mechanism in colorectal cancer (CRC) are unclear. The present study aimed to identify the potential targets of ASP for CRC treatment using network pharmacology and explore its possible therapeutic mechanisms using in vitro and in vivo experiments. The active compounds and potential targets of ASP were obtained from the TCMSP database, followed by CRC-related target genes identification using GeneCards and OMIM databases, which were matched with the potential targets of ASP. Based on the matching results, potential targets and signaling pathways were identified by protein-protein interaction (PPI), gene ontology (GO) functions, and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses. Finally, in vitro and in vivo experiments were performed to further validate the anti-cancer effects of ASP on CRC. Network pharmacology analysis identified nine active components from ASP from the database based on oral bioavailability and drug similarity index, and 157 potential targets related to ASP were predicted. The PPI network identified tumor protein 53 (TP53), Fos proto-oncogene, AP-1 transcription factor subunit (FOS), and AKT serine/threonine kinase 1 (AKT1) as key targets. GO analysis showed that ASP might act through response to wounding, membrane raft, and transcription factor binding. KEGG enrichment analysis revealed that ASP may affect CRC through the phosphatidylinositol-4,5-bisphosphate 3-kinase PI3K/AKT/mechanistic target of rapamycin kinase (mTOR) signaling pathway. In vitro, ASP inhibited cell proliferation, migration, and invasion of HCT116 and LOVO cells, and caused G0/G1 phase arrest and apoptosis in CRC cells. In vivo, ASP significantly inhibited the growth of CRC transplanted tumors in nude mice. Furthermore, pathway analysis confirmed that ASP could exert its therapeutic effects on CRC by regulating cell proliferation and survival through the PI3K/AKT/mTOR signaling pathway. This study is the first to report the potential role of ASP in the treatment of colorectal cancer.